Bioengineered Biomimetic and Bioinspired Noninvasive Drug Delivery Systems. (14th July 2021) - Rahamim, Valeria; Azagury, Aharon
Abstract: The main purpose herein is to provide an up‐to‐date review on noninvasive biomimetic, bioinspired, and bioengineered drug delivery system (DDS). Noninvasive DDS is an ever‐growing field critical for the applicability of drugs. It offers noninvasive administration routes with improved controlled, targeted, and triggered drug delivery. Noninvasive DDS employ many approaches and strategies, such as, nano‐ and microparticles, lipid‐based systems, sonophoresis, electrophoresis and iontophoresis, penetration enhancers, microneedles, and gels. The last decade seen a surge in research papers employing the paradigms of biomimicry, bioinspiration, and bioengineering. However, since the use of these terms in noninvasive DDS field is often inconsistent and unclear, some generalized perspectives are provided on the possible usage of these terms in future publications. Additionally, a critical discussion on the novelty and origins of these paradigms is provided. The advantages and disadvantages of each of the noninvasive routes and their current main limitations are summarized. The main aspects of indicated fields are discussed: The unique physiology of the related tissues, the main hurdles for mass transport, the various DDS tested, and materials selection. Finally, the basic concepts and therapeutic effects of these DDS are discussed and future venues for noninvasive biomimetic, bioinspired, and bioengineered DDS research are proposed. Abstract : Various strategies used in noninvasive biomimetic, bioinspired, and bioengineered drug delivery systems (DDSs) are described. Details are provided on the unique physiology of related tissues, main hurdles for mass transport, and materials selection. A discussion on the novelty and origins of these paradigms is provided, and the future venues for biomimetic, bioinspired, and bioengineered noninvasive DDS research are proposed.